A review of the coelidiine leafhopper genus Mahellus (Hemiptera: Cicadellidae: Coelidiinae) with description of two new species from the Oriental region - Viraktamath, C.a.; Meshram, Naresh M. (Zootaxa, 2017)
Two new species of the genus Mahellus Nielson, M. cardoni sp. nov. (Indonesia: Sulawesi) and M. ungulatus sp. nov. (India: Kerala, Karnataka, Tamil Nadu) are described and illustrated. M. distanti Nielson is also illustrated with several new locality records. A key for the four known species of the genus is also given.